Exploration of the phonological consciousness and the speed of nominated in students of 3º education infantil and 1º of primary education and its relation with the learning of the lectoscritura - Mª José Rabazo Méndez; María García López; Susana Sánchez Herrera (INFAD, 2016)
This article presents a descriptive cross-sectional study comparing the performance in phonemic awareness skills and efficiency in naming letters, numbers, colours and digits in a group of preliterate children as compared to another group of initiated readers. 45 children, 20 from 3rd year of Nursery Education and 25 from 1st year of Primary Education were evaluated using the Rapid  Automatized Naming Test (RAN) and the Test of Phonological Knowledge Assessment (CEEC). Mean comparisons and Pearson correlation contrasts were performed to assess the difference between the groups and to analyse the interrelationships between the variables. The results show significant differences between the two groups, being the students from Primary Education the ones obtaining the best results. This data would be in line with studies on the directionality of causality between phonological awareness and learning to read in the sense that the systematic teaching of reading favours phonological awareness at a phonemic level as well as with those that have revealed the relationship between phonological awareness and rapid naming.